PENERAPAN ANALISIS METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM PENGENDALIAN BIAYA PERSEDIAAN BAHAN BAKU PADA CV. SILVER CONVECTION BANJARANYAR PACIRAN LAMONGAN - Agus Wahid Suyoto (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the inventory control of raw materials for fabric at CV. Silver Convection and to determine the level of inventory cost efficiency through the application of the Economic Order Quantity (EOQ) method. The type of research used is descriptive research with a quantitative approach. The data used consists of primary and secondary data obtained through interviews, observations, and literature studies. The results of the study indicate that the raw material inventory control implemented by the company so far is inefficient, characterized by a high ordering frequency and the absence of safety stock. Based on the EOQ method calculation, the optimal order quantity is 333 rolls per order with an ordering frequency of 3 times per year. In addition, a safety stock of 123 rolls and a reorder point of 205 rolls are obtained. The application of the EOQ method is able to reduce the total cost of raw material inventory from Rp1,430,000 to Rp497,900, resulting in a cost efficiency of Rp932,100. Thus, the EOQ method is proven to be more effective and efficient in controlling raw material inventory at CV. Silver Convection.